2009
DOI: 10.1128/jvi.01891-08
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Characterization of a Single-Cycle Chimeric Flavivirus Vaccine Candidate That Protects Mice against Lethal Challenge with Dengue Virus Type 2

Abstract: We have previously described a novel flavivirus vaccine technology based on a single-cycle, capsid (C) gene-deleted flavivirus called RepliVAX. RepliVAX can be propagated in cells that express high levels of C but undergoes only a single cycle of infection in vaccinated hosts. Here we report that we have adapted our RepliVAX technology to produce a dengue vaccine by replacing the prM/E genes of RepliVAX WN (a West Nile virus [WNV] RepliVAX) with the same genes of dengue virus type 2 (DENV2). Our first RepliVAX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…Thus, we showed that the NS2B/3 cleavage at the C terminus of protein C is not required when protein C is present on the same polyprotein as the other viral proteins. This is in good agreement with previous work that obviated the need for NS2B/3 cleavage of protein C by supplying protein C from separate translation units (10,13,27,36,40,42). The viruses in such experiments replicated to high titers; therefore, it seems likely that interference with the NS2B/3 cleavage on protein C has only a minor effect on the efficiency of viral replication.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, we showed that the NS2B/3 cleavage at the C terminus of protein C is not required when protein C is present on the same polyprotein as the other viral proteins. This is in good agreement with previous work that obviated the need for NS2B/3 cleavage of protein C by supplying protein C from separate translation units (10,13,27,36,40,42). The viruses in such experiments replicated to high titers; therefore, it seems likely that interference with the NS2B/3 cleavage on protein C has only a minor effect on the efficiency of viral replication.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, previous investigations of the C-terminal region of TBEV protein C revealed remarkable functional flexibility in the exact NS2B/3 cleavage position, as well as the cleavage substrate (35). In addition, several groups have also been able to supply protein C in trans to allow single-round infectious particles of several flaviviruses to be generated (10,13,27,36,40).…”
mentioning
confidence: 99%
“…Another advantage of the replicons are the different ways in which they can be used as immunizing: DNA, RNA or defective particles (Varnavski et al 2000, Aberle et al 2005, Suzuki et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Frey et al [112] and Suter et al [113] employed VRP based on the classical swine fever virus genome, demonstrating that a single inoculation was efficient at inducing both humoral and cellular immunity. Flavivirus replicons, such as those derived from West Nile fever virus, have been modified to deliver genes of dengue virus type 2 [114]. Again, a single inoculation was sufficient to induce anti-dengue-virus neutralizing antibodies and the animals showed increased resistance to challenge infection.…”
Section: Rnaimentioning
confidence: 99%